UNEMPLOYMENT IN NIGERIA: A TIME BOMB WAITING TO EXPLODE: ISSUES, DIAGNOSES AND THE WAY FORWARD - Chiazor, I. A; zoya, M. I.; Udume, M. (Advances in Social Sciences Research Journal, 2017)
The incidence of unemployment in Nigeria in this 21st ce ntury is alarming. Over 80% of graduates from higher institutions in Nigeria are unemploy ed , this is in spite of their qualifications . The inability of the higher educational institutions to meet the needs of these graduates, as well as promote their economic self- reliance and self- sufficiency has resulted inmassive unemployment in Nigeria. Unemployment constitutes a serious developmental problem and is increasing at an alarming rate all over Nigeria. It hinders the growth of the economy as it affects the socio-economic and political aspects of life. Unemployment leads to poverty. The paper examines the causes of unemployment in Nigeria and i ts effects on the economy. It identifies those who are mostly affected by the unemployme nt scourge. This thesis relied mainly on secondary sources of data gleaned from existing literatur e on the causes of unemployment and suggests possible solutions to the unemployment bomb that is waiting to explode in Nigeria. The paper believes that education is critical to making Nigerian youths more employable. It also holds the view that there is need for the army of the unemployed in Nigeria to embrace skill acquisition. Furthermore, the agricultural sector must be transformed as this will enhance their choice base and bring about massive job opportunities in that sector.